Peran Perempuan dalam Tradisi Sedekah Gunung di Desa Pelangas, Kecamatan Simpang Teritip, Kabupaten Bangka Barat - Saputra, Putra Pratama; Ramadhani, Tiara; Sinabutar, Michael Jefri (Paradigma: Jurnal Kajian Budaya, 2021)
Women have a role in a particular culture, and this can serve as a way to express their freedom and to be on an equal footing with their male counterparts. The Jering ethnic group in Palangas Village, Bangka Island, has a traditional ritual that is still carried out by the community, namely sedekah gunung. This ritual is carried out once a year, coinciding with the 14th night of the full moon. This ritual serves as an expression of gratitude for the good harvest that occurred for the entire year. This study used the descriptive qualitative method, while data collection techniques included interviews, observations, and documentation. The focus of this research is the role of women in the sedekah gunung ritual. There are several roles and functions that women serve both before and after the ritual. Just like cooking, which is predominantly done by women, the campak dambus dance is also performed by women in cultural arts performances, while the tabuh dance is also part of a series of rituals during the sedekah gunung. Women’s roles in such rituals, as well as the belief surrounding them, show that they always do things that are considered good according to the local custom. Our observation shows that the role of women is still very dominant in the ritual even though some roles have been taken over by men. The role of women in the ritual almost equals the role of men, and the involvement of women in the tradition can greatly contribute to the preservation of the tradition so that it can continue to this day.